2003
DOI: 10.1038/sj.hdy.6800218
|View full text |Cite
|
Sign up to set email alerts
|

The FMR1 CGG repeat and linked microsatellite markers in two Basque valleys

Abstract: Fragile X syndrome is associated with an unstable CGG repeat sequence in the 5 0 untranslated region of the first exon of the FMR1 gene. The present study involved the evaluation of factors implicated in CGG repeat stability in a normal sample from two Basque valleys (Markina and Arratia), to discover whether the Basque population shows allelic diversity and to identify factors involved, by using the data in conjunction with previous findings. The study was based on a sample of 204 and 58 X chromosomes from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…In the present study, we characterised the microsatellite markers DXS548, FRAXAC1 and FRAXAC2, the ATL1 SNP and the corresponding haplotypes in a mentally retarded male population from Latvia with normal and expanded FMR1 gene CGG repeats. Previous studies have suggested linkage of CGG tract instability with the G allele of ATL1, specific microsatellite marker haplotypes and a CGG tract AGG interspersion pattern exhibiting a long uninterrupted CGG repeat at the 3' end [5,11,[22][23][24][25]. Our results revealed a statistically significant prevalence of the G allele of ATL1 among grey zone alleles and full mutation alleles as an indicator of instability.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In the present study, we characterised the microsatellite markers DXS548, FRAXAC1 and FRAXAC2, the ATL1 SNP and the corresponding haplotypes in a mentally retarded male population from Latvia with normal and expanded FMR1 gene CGG repeats. Previous studies have suggested linkage of CGG tract instability with the G allele of ATL1, specific microsatellite marker haplotypes and a CGG tract AGG interspersion pattern exhibiting a long uninterrupted CGG repeat at the 3' end [5,11,[22][23][24][25]. Our results revealed a statistically significant prevalence of the G allele of ATL1 among grey zone alleles and full mutation alleles as an indicator of instability.…”
Section: Discussionsupporting
confidence: 62%
“…Grey zone alleles with a long uninterrupted CGG tract at the 3' end associated with this haplotype have a higher likelihood of increasing the number of CGG repeats, leading to premutation or mutation over generations. Several studies have identified specific haplotypes associated with FXS patients and normal CGG repeat alleles across European populations [22,[25][26][27][28][29]. However, only a limited number of these studies focused on populations from Eastern and Northeastern Europe.…”
Section: Discussionmentioning
confidence: 99%
“…The more studied are flanking microsatellites and (SNPs). Mutated alleles are in linkage disequilibrium with flanking microsatellite markers, like DXS548 and FRAXAC1 [66]. It has also been suggested that SNPs can proportionate an advance in the study of CGG repeat instability.…”
Section: Fmr1 Genementioning
confidence: 99%
“…Subsequent investigations on the FMR1 gene among a normal sample of Basque origin from the Biscay province and other Basque provinces showed a low frequency of large alleles and the maintenance of AGG interruptions on them (Arrieta et al, 1999b; Peñagarikano et al, 2004). In another previous work (Arrieta et al, 2003), we extended our study to Markina and Arratia, two different and isolated Basque valleys from the Biscay province. The results obtained showed differences between Markina and Arratia with respect to factors involved in CGG repeat instability and also a great similarity between the general Basque sample from the Biscay province and that from the Markina valley.…”
Section: Introductionmentioning
confidence: 99%